Some Linguistic Implications of Transferring Rituals Online The Case of bay?ah or Allegiance Pledging in Sufism. - Rosowsky, A.
Within the growing body of research devoted to exploring digital religion (), relatively little attention has been paid to the linguistic implications of religion moving online. In a study focusing on the online ritual of bay?ah, or allegiance pledging, in Sufism, this article presents findings that identify instances of language form and practice being modified and transformed when ritual moves online. Two aspects of linguistic change are considered. The first explores how an offline, predominantly orally based ritual transfers to a predominantly visual and written mode of communication online. The second considers how ritual performativity is maintained, modified or reduced as a consequence of this transfer. Using a combination of multimodal discourse analysis and speech act theory, an analysis of the findings suggests that a variety of approaches are used by designers of online ritual portals to address these linguistic challenges.